Wanderlust [videorecording (DVD)] - Apatow, Judd, 1967-; Wain, David, 1969-; Aniston, Jennifer; Alda, Alan, 1936-; Rudd, Paul; Akerman, Malin, 1978-; Theroux, Justin (Universal Studios Home Entertainment, 2012)
After George loses his high-stress Manhattan job, he and his wife Linda hit the road and wind up crashing at Elysium, a free-spirited community of hippies, tree-huggers, and the occasional nudist.